Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Certainly! Let's solve the equation step by step.
1. Start with the given equation:
[tex]\[ 2(3x - 2.7) = 3x - 5.4 \][/tex]
2. Distribute the 2 on the left-hand side:
[tex]\[ 2 \cdot (3x) - 2 \cdot 2.7 = 3x - 5.4 \][/tex]
Simplifying the multiplications:
[tex]\[ 6x - 5.4 = 3x - 5.4 \][/tex]
3. Now, we have:
[tex]\[ 6x - 5.4 = 3x - 5.4 \][/tex]
4. To isolate the [tex]\( x \)[/tex] terms, subtract [tex]\( 3x \)[/tex] from both sides of the equation:
[tex]\[ 6x - 3x - 5.4 = 3x - 3x - 5.4 \][/tex]
Simplifying this:
[tex]\[ 3x - 5.4 = -5.4 \][/tex]
5. Next, add 5.4 to both sides to isolate the [tex]\( x \)[/tex] term:
[tex]\[ 3x - 5.4 + 5.4 = -5.4 + 5.4 \][/tex]
Simplifying this:
[tex]\[ 3x = 0 \][/tex]
6. Finally, divide both sides by 3 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{0}{3} \][/tex]
Simplifying:
[tex]\[ x = 0 \][/tex]
Therefore, the solution to the equation [tex]\( 2(3x - 2.7) = 3x - 5.4 \)[/tex] is:
[tex]\[ x = 0 \][/tex]
1. Start with the given equation:
[tex]\[ 2(3x - 2.7) = 3x - 5.4 \][/tex]
2. Distribute the 2 on the left-hand side:
[tex]\[ 2 \cdot (3x) - 2 \cdot 2.7 = 3x - 5.4 \][/tex]
Simplifying the multiplications:
[tex]\[ 6x - 5.4 = 3x - 5.4 \][/tex]
3. Now, we have:
[tex]\[ 6x - 5.4 = 3x - 5.4 \][/tex]
4. To isolate the [tex]\( x \)[/tex] terms, subtract [tex]\( 3x \)[/tex] from both sides of the equation:
[tex]\[ 6x - 3x - 5.4 = 3x - 3x - 5.4 \][/tex]
Simplifying this:
[tex]\[ 3x - 5.4 = -5.4 \][/tex]
5. Next, add 5.4 to both sides to isolate the [tex]\( x \)[/tex] term:
[tex]\[ 3x - 5.4 + 5.4 = -5.4 + 5.4 \][/tex]
Simplifying this:
[tex]\[ 3x = 0 \][/tex]
6. Finally, divide both sides by 3 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{0}{3} \][/tex]
Simplifying:
[tex]\[ x = 0 \][/tex]
Therefore, the solution to the equation [tex]\( 2(3x - 2.7) = 3x - 5.4 \)[/tex] is:
[tex]\[ x = 0 \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.